THE EFFECTIVENESS OF USING INTERACTIVE QUIZ IN IMPROVING ENGLISH SPEAKING SKILL AT SMP NEGERI 2 SUNGGUMINASA - Masnur, Fildah Aini; Abduh, Amirullah; Baa, Sultan (Universitas Negeri Makassar, 2025)
The purpose of this study was to determine the effectiveness of using an interactive quiz (Quizizz application) in improving the speaking ability of grade nine students at SMP Negeri 2 Sungguminasa. This study is a Pre-experimental involving one class that was given special treatment. The population in this study was grade nine students of SMP Negeri 2 Sungguminasa consisting of 11 classes, the sample in this study from the population using the cluster random sampling method, where one class was randomly selected, namely class X5 consisting of 30 students. The data collection process involved giving a speaking test before treatment and a speaking test after treatment. The data collected from the oral speaking test was analyzed quantitatively using the IBM SPSS Version 22 application and used to compare the test results. Pre-test and post-test using paired sample t-test. The results of the analysis showed the average score of the pre-test was 41.33 with a classification of “poor” and the average score of the post-test was 72.4 with a classification of “good”. Based on this study, the results of the hypothesis t-test showed a significance value of <000, which is lower than the significance level of 0.05. The results of the pre-test and post-test obtained t-table 2.0481 df 28, and p<000, there is a significant effect of using the quizizz application in improving English speaking skills of the grade nine students at SMP Negeri 2 Sungguminasa.